Impact of Fatwa Upon Bank Interest ban On The Development of Islamic Banking in Indonesia - Diana Ambarwati (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2021)
The purpose of this article is to describe the impact of bank interest ban fatwa on the development of Islamic Banks in Indonesia. Fatwa of the Indonesian Ulama Council number 1 of 2004 is the basis for various parties to contribute to realizing competitive Islamic banking. This fatwa has encouraged the Government to issue various rules in the form of laws and government regulations related to banking. The issuance of this rule is a serious proof of the government’s commitment to provide more space for the development of Islamic banking in Indonesia, in addition to being a proof of appreciation for the issuance of bank interest ban fatwa by the Indonesian Ulema Council. In addition, the bank’s fatwa on the ban on bungan has encouraged the role of the community to contribute real to the development of Islamic banking. The emergence of the Association of Islamic Economists (IAEI), sharia economic community (MES), the National Committee of Islamic finance which is now renamed to the National Committee of Islamic Economics and Finance (KNEKS) is a concrete evidence of community contribution to socialize and strengthen Islamic banking.